Intravasation Affects the Diagnostic Image Quality of Transvaginal 4‐Dimensional Hysterosalpingo‐Contrast Sonography With SonoVue. (31st December 2018) - He, Yanni; Wu, Haorong; Xiong, Ran; Liu, Hongmei; Shi, Jiayao; Xu, Jingjiao; Zhang, Ning; Liu, Yu
Abstract : Objectives: We aim to retrospectively analyze the diagnostic image quality of transvaginal 4‐dimensional hysterosalpingo‐contrast sonography from infertile patients and determine the significant influencing factors. Methods: A total of 445 patients visiting infertility clinics were included in the study, of which 167 were primary infertile and 278 were secondary infertile. The factors were recorded, including age; examination time; infertility type; history of pelvic inflammatory disease, pelvic surgery, intrauterine surgery, and ectopic pregnancy; endometrial thickness; uterine position; ovarian position; 2‐dimensional image quality; intravasation quantity, position, and time; balloon volume; and the dosage of contrast agent or the sterile saline solution. All the factors were compared among different diagnostic image quality groups. The method of rank logistic regression analysis was adopted to analyze the risk factors affecting the diagnostic image quality. Results: Among the 445 infertile patients, 124 (27.9%) patients had intravasation occur during transvaginal 4‐dimensional hysterosalpingo‐contrast sonography. The diagnostic image quality between the 2 sonographers was consistent (Cronbach's alpha, 0.993). Different intravasation quantities, positions, and times; increased of balloon volume; and history of pelvic surgery were substantial risk factors for the diagnostic image quality. The diagnostic image quality diminished with the increase of intravasation. In the patient with cornual intravasation, the diagnostic image quality was substantially worse than that with non–cornual intravasation. Moreover, early onset of intravasation seriously affected the diagnostic image quality. Conclusions: In conclusion, intravasation affected the diagnostic image quality, especially early cornual massive intravasation.